Hybrid Feel-Own-Move®: protocol for an effectiveness-implementation study of a psychomotor intervention for survivors of domestic violence - Machorrinho, Joana; Veiga, Guida; Marmeleira, José; Scheffers, Mia; Santos, Graça Duarte (Frontiers in Public Health, 2025)
BackgroundDomestic violence is a public health concern, impacting the health and well-being of women and children globally. Shelter homes are one of the support services for victims’ recovery, although providing holistic healthcare in this setting remains a struggle. Feel-Own-Move® (FOM) is an evidence-based psychomotor intervention designed to help women who have experienced domestic violence reconnect with their bodies. Hybrid FOM (H-FOM) is a version of FOM that combines in-person with online sessions for both women and children living in shelter homes. To examine the effectiveness and implementation success of H-FOM are the aims of this study.MethodsThis protocol details an effectiveness-implementation type I hybrid study, to be carried out in shelter homes across three European countries. Health outcomes of the participants, and the implementation success within professionals from the shelter homes and the psychomotor therapists responsible for implementing H-FOM will be assessed. Results will be analyzed through a mixed methods approach, following the conceptual model of implementation science and the RE-AIM framework.DiscussionThis effectiveness-implementation study is expected to contribute to understanding H-FOM health-related effects on women and children survivors of violence, as well as to its sustainable implementation, up-scaling and integration into trauma support services and associated healthcare policy. H-FOM is expected to (i) improve the known effects of FOM on women survivors of DV, while ensuring continuity of the therapeutic process following relocation, and promoting the health and well-being of children living in the shelter homes.